Correlation between the number and duration time of meals and the presence of gastrointestinal signs in patients with more than 24 months of bariatric surgery - Conceição, Weany Jacqueline Costa da (2022)
Introduction: Obesity is a complex chronic illness defined by a positive energy balance between excessive food consumption and energy expenditure, resulting in an excessive growth of adipose tissue. Bariatric surgery, which involves excision and stomach reconstruction, improves nutritional status and quality of life. Objective: The goal of this study is to find a link between the number and duration of meals and the occurrence of gastrointestinal symptoms in individuals who have had bariatric surgery for more than 24 months. Materials and Methods: This was a cross-sectional, descriptive, and analytical study of women between the ages 18 to 59 years who had had bariatric surgery at least two years before the beginning of the study, utilizing RYGB or Vertical Gastrectomy as surgical procedures. During consultations, data were collected using a questionnaire. Results: The analysis revealed that (66%) of the applicants experienced dumping syndrome, with the other most often reported symptoms being nausea (40%), vomiting (24%), and food intolerance (58%), with reduced tolerance to meat, milk, and sweets/sugar. There was also acceptable weight reduction following surgery, although most patients experienced considerable weight rebound. Conclusion: There was an inversely significant relationship between dysphagia and dyspepsia and mealtimes, as well as an inversely significant relationship between vomiting and number of meals. In terms of the anthropometric profile, a direct link between excess weight loss and number of meals was discovered, as well as an inverse correlation between weight recovery and number of meals.